SAFESPEAK: AN ANONYMOUS DIGITAL MENTAL HEALTH COMPANION FOR PAKISTANI TEENAGERS - Sasuee Rajper,; Kandeel Fatima ,; Saleha Memon,; Mohsin Ali Shah Syed,; Sayeda Rubab Fatima, (Spectrum of Engineering Sciences, 2025)
Mental health issues among adolescents in Pakistan are increasingly prevalent, with more than half of the youth experiencing symptoms of anxiety and depression. Despite the seriousness of the problem, societal stigma, lack of awareness, and limited access to mental health services prevent many young individuals from seeking help. This research introduces Safe Speak, a culturally adapted, AI-powered anonymous chat platform designed specifically to support teenagers dealing with mental health challenges in Pakistan. The platform leverages Natural Language Processing (NLP) to facilitate empathetic conversations, detect emotional distress, and escalate serious cases to trained human counselors. By offering privacy, accessibility, and anonymity, Safe Speak aims to provide a safe and judgment-free space for adolescents to express their concerns. This paper explores conceptual design, existing literature on digital mental health interventions, and the proposed implementation framework. It also discusses the potential impact, benefits, and limitations of such a platform within Pakistan’s socio-cultural landscape. SafeSpeak represents a novel, scalable solution for bridging the mental health care gap for Pakistani youth, particularly those in underserved or rural areas.